2016
DOI: 10.29122/jstmc.v17i1.544
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kejadian El Nino Tahun 2015 Dan Pengaruhnya Terhadap Peningkatan Titik Api Di Wilayah Sumatera Dan Kalimantan

Abstract: IntisariKejadian El Nino yang berdampak pada sebagian besar wilayah Indonesia akan selalu berasosiasi dengan kekeringan akibat dari berkurangnya intensitas curah hujan. Lebih jauh akibat dari kekeringan tersebut telah menimbulkan meningkatnya titik api secara signifikan dibandingkan dengan tahun-tahun sebelumnya khususnya di wilayah Sumatera dan Kalimantan, dimana hal tersebut telah mengakibatkan terjadinya bencana asap pada tahun 2015. Tujuan utama penulisan karya tulis ini adalah untuk menganalisis kejadian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
1
5
0
2
Order By: Relevance
“…Therefore, the number of total hotspots in 1 drought season nearly double the moderate El Niño year. The results obtained are similar to Yananto and Dewi (2016) study where the number of hotspots continues to increase from July to October in both regions. In November 2015, the number of hotspots had decreased drastically in line with the increase amount of rainfall (Yananto and Dewi 2016).…”
Section: Kalimantansupporting
confidence: 87%
“…Therefore, the number of total hotspots in 1 drought season nearly double the moderate El Niño year. The results obtained are similar to Yananto and Dewi (2016) study where the number of hotspots continues to increase from July to October in both regions. In November 2015, the number of hotspots had decreased drastically in line with the increase amount of rainfall (Yananto and Dewi 2016).…”
Section: Kalimantansupporting
confidence: 87%
“…The research focusing on the mapping of smoke from forest and land fires was conducted in the regions of South Sumatra, Jambi, and Central Kalimantan (Figure 1). In 2015 and 2019, Indonesia experienced the El-Nino phenomenon, leading to widespread forest and land fires across the country, affecting almost all regions, with Kalimantan and Sumatra being the most severely impacted areas 23,24 . Specifically, the provinces of South Sumatra, Jambi, and Central Kalimantan were among the three provinces that were most affected by the fires during that period.…”
Section: Study Areamentioning
confidence: 99%
“…Location outside the Niño region were ignored even though they have a high spatial correlation value. Previ- ous researches revealed that the Niño region may affect the rainfall variability in Indonesia (Hidayat et al, 2018;Nabilah et al, 2017;Pan et al, 2018;Qalbi et al, 2017;Yananto and Dewi, 2016). Therefore, the predictor coordinates were only taken in the Niño region.…”
Section: Spatial Correlationmentioning
confidence: 99%
“…SST has a strong effect on rainfall in Indonesia from the dry season to the transitional season, between April -November (Hidayat and Ando, 2014). Fluctuation of sea surface temperature in the Niño 3, 3.4, and 4 region will affect rainfall in Indonesia (Yananto and Dewi, 2016), such as rainfall in Central Java (Hidayat et al, 2018), West Java (Nabilah et al, 2017), Banten (Mulyaqin, 2020), Sulawesi (Prasetyo and Pusparini, 2018), and Sumatra (Qalbi et al, 2017). More specifically, the rainfall in Banda Aceh City and Aceh Besar District is also related to the variability of the Pacific sea surface temperature both in normal and extreme climate conditions (Ilhamsyah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%